Methods for the synthesis of barium titanate as a component of functional dielectric ceramics - A. A. Kholodkova; A. V. Reznichenko; A. A. Vasin; A. V. Smirnov (Тонкие химические технологии)
Objectives. To examine the general principles and recent advances in the synthesis of high-purity and high-homogeneity barium titanate powders in the manufacture of electronic components.Results. The main publications regarding the synthesis of barium titanate powder, including the works of recent years, were analyzed. The technological advantages and disadvantages of various synthesis methods were identified. Groups of methods based on solid-state interaction of reagents and methods of “wet chemistry” were also considered. The possibilities of producing barium titanate particles of non-isometric shapes for creating textured ceramics were discussed separately.Conclusions. Barium titanate is a well-known ferroelectric with a high dielectric constant and low dielectric loss. It is used as a component in ceramic electronic products, for example, capacitors, memory devices, optoelectronic devices, and piezoelectric transducers. The possibilities of producing functional ceramics based on barium titanate powder largely depend on its state and morphological characteristics, determined during the synthesis stage. The most important factors affecting the functional characteristics of ceramics are the purity and morphology of the powder raw materials used.